1997
DOI: 10.1128/jb.179.8.2595-2607.1997
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of genes of Pseudomonas sp. strain HR199 involved in bioconversion of vanillin to protocatechuate

Abstract: The gene loci vdh, vanA, and vanB, which are involved in the bioconversion of vanillin to protocatechuate by Pseudomonas sp. strain HR199 (DSM 7063), were identified as the structural genes of a novel vanillin dehydrogenase (vdh) and the two subunits of a vanillate demethylase (vanA and vanB), respectively. These genes were localized on an EcoRI fragment (E230), which was cloned from a Pseudomonas sp. strain HR199 genomic library in the cosmid pVK100. The vdh gene was identified on a subfragment (HE35) of E230… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
178
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(185 citation statements)
references
References 55 publications
7
178
0
Order By: Relevance
“…In contrast, the abundance of amyA, nplT, pulA, pectinase, ara_fungi, mannanase, and xylA associated with the degradation of labile C (starch, pectin, or hemicellulose) decreased in post-grazing grassland soils of the 3400-m site, whereas those of vdh, vanA, glx, and lip associated with degradation of recalcitrant C (aromatics or lignin) increased (Fig. 3b), suggesting a shift from use of labile C toward recalcitrant C. The vdh and vanA genes associated with the bioconversion of vanillin to protocatechuate for aromatics degradation were abundant in Pseudomonas sp., which was consistent with the results of a previous study (Priefert et al 1997). The most abundant lip gene was similar to the sequence from Trametes versicolor, which was shown to play an important role in lignin oxidation (Bourbonnais et al 1995;Johansson and Nyman 1993).…”
Section: Major Environmental Attributes Influencing Microbial Communitysupporting
confidence: 82%
“…In contrast, the abundance of amyA, nplT, pulA, pectinase, ara_fungi, mannanase, and xylA associated with the degradation of labile C (starch, pectin, or hemicellulose) decreased in post-grazing grassland soils of the 3400-m site, whereas those of vdh, vanA, glx, and lip associated with degradation of recalcitrant C (aromatics or lignin) increased (Fig. 3b), suggesting a shift from use of labile C toward recalcitrant C. The vdh and vanA genes associated with the bioconversion of vanillin to protocatechuate for aromatics degradation were abundant in Pseudomonas sp., which was consistent with the results of a previous study (Priefert et al 1997). The most abundant lip gene was similar to the sequence from Trametes versicolor, which was shown to play an important role in lignin oxidation (Bourbonnais et al 1995;Johansson and Nyman 1993).…”
Section: Major Environmental Attributes Influencing Microbial Communitysupporting
confidence: 82%
“…l), which undergoes ring fission by the ortho pathway. T h e genetics of the pathway from vanillic acid to protocatechuic acid have been described by Brunel & Davison (1988) and also recently by Priefert et al (1997). Both studies showed that t w o proteins (VanA and VanB) form a vanillate demethylase complex which demethylates vanillic acid to protocatechuic acid.…”
Section: E N T U R I a N D O T H E R Smentioning
confidence: 99%
“…Phenolic acids also serve as a signal and induce virulence gene expression in the plant-associated Agrobacterium tumefaciens [20]. Some Pseudomonas strains as well as Acinetobacter calcoaceticus are able to use these acids as the sole source of carbon for growth [17,24,28,30]. Moreover, ferulic acid is exploited to produce value-added aromatic compounds, such as vanillin.…”
Section: Introductionmentioning
confidence: 99%